2020
DOI: 10.1097/qco.0000000000000612
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics to manage inflammation in HIV infection

Abstract: Enzyme-linked immunosorbent assay (ELISA) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 276 publications
1
11
0
Order By: Relevance
“…There are several approaches proposed for managements of chronic inflammation and immune activation in PLHIV. However, results from clinical trials on the use of conventional and unconventional anti-inflammatory agents as well as probiotics [ 25 , 26 ], are promising but remain unsatisfactory [ 27 30 ]. In this study, we observed that relationship between markers of inflammation varied with treatment status.…”
Section: Discussionmentioning
confidence: 99%
“…There are several approaches proposed for managements of chronic inflammation and immune activation in PLHIV. However, results from clinical trials on the use of conventional and unconventional anti-inflammatory agents as well as probiotics [ 25 , 26 ], are promising but remain unsatisfactory [ 27 30 ]. In this study, we observed that relationship between markers of inflammation varied with treatment status.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that HIV and SIV utilize the microbiota to develop their pathogenesis as well [90]. Moreover, we should again mention that in spite of these many studies which support the idea of beneficial role of microbiota on HIV infection, there are also studies which have not supported this idea [122]. As the last example, vaginal dysbiosis increases in IL-33 which is an alarming compound for epithelial damages, then inhibits T cells migration to vaginal lymphoid tissues, so it can't secret antiviral interferons and cytokines and let HSV infection to promote [121,123].…”
Section: Promotionmentioning
confidence: 91%
“…Recent studies suggest that probiotic bacteria have a beneficial role in HIV patients during antiretroviral treatment via maintaining microbiota composition, reducing mucosal and systemic inflammation, stimulating natural killer cell, increasing macrophage phagocytic activity, stimulating interferon-γ, interleukin (IL)-12, and IL-18 and improving intestinal barrier [100,[119][120][121]. In spite of these many studies, which support the idea of beneficial role of microbiota on HIV infection, there are also studies which did not support this [122]. As the last example, vaginal dysbiosis increases in IL-33, which is an alarming compound for epithelial damages, then inhibits T cells migration to vaginal lymphoid tissues, so it can't secret antiviral interferons and cytokines and thereby promotes HSV infection [121,123].…”
Section: The Gut Microbiota Role In Stdmentioning
confidence: 99%
“…Manipulation of the intestinal microbiota by probiotic therapy could improve musical immune responses. Previous studies have confirmed that probiotics are well-tolerated by anti-retroviral therapy (ART)-treated HIV-infected individuals, although the overarching conclusions varied between studies 15 . Indeed, several groups demonstrated marked improvement with probiotic therapy, including reduced peripheral and intestinal frequencies of activated CD4 + T cells 16,17 and lower levels of inflammatory markers in the CNS 18 .…”
Section: Introductionmentioning
confidence: 99%